Nghiên cứu một số vấn đề của dự án Luật Nhà ở (sửa đổi);đề xuất, kiến nghị hoàn thiện Luật - Nguyễn Thị Giang (2023)
|Tác giả Nghiên cứu một số vấn đề của dự án Luật Nhà ở (sửa đổi);đề xuất, kiến nghị hoàn thiện Luật